2021
DOI: 10.1101/2021.08.17.456634
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extracellular cues accelerate neurogenesis of induced pluripotent stem cell derived neurons

Abstract: Neurogenesis is a complex process encompassing neuronal progenitor cell expansion/proliferation and differentiation, followed by neuron maturation. In vivo models are most commonly used to study neurogenesis; however, human induced pluripotent stem cell-derived (iPSC) neurons are increasingly used to establish cellular models of human neurological processes. Unfortunately, the differentiation and maturation of iPSC-derived neurons varies in methodology, is asynchronous, and has restricted experimental utility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…Neuronal progenitor cell culturing and maintenance was carried out as described using the 7753 NPC line [22,23]. Briefly, NPCs were maintained on Matrigel™‐coated dishes in complete NPC medium [i.e., DMEM‐F12 supplemented with Glutamax (Gibco, Gaithersburg, MD, USA), 2% B27 without vitamin A (Gibco) and 20 ng·mL −1 thermostable recombinant human Fibroblast Growth Factor (Gibco)] in 5% CO 2 and environmental O 2 at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Neuronal progenitor cell culturing and maintenance was carried out as described using the 7753 NPC line [22,23]. Briefly, NPCs were maintained on Matrigel™‐coated dishes in complete NPC medium [i.e., DMEM‐F12 supplemented with Glutamax (Gibco, Gaithersburg, MD, USA), 2% B27 without vitamin A (Gibco) and 20 ng·mL −1 thermostable recombinant human Fibroblast Growth Factor (Gibco)] in 5% CO 2 and environmental O 2 at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies [22], we established neuronal culturing conditions that resulted in the expression of neuronal maturation markers such as NeuN, calbindin, tau, and calretinin at 4 weeks post-differentiation while in asynchronous culture. Subsequent analyses of Ki67 expression in 4-week maturing cultures, in contrast to 2-week (i.e., differentiating cultures) suggested that these neuronal cultures were no longer engaged in the cell cycle [22,23].…”
Section: Maturing Ipsc-derived Neuron Cultures Exhibit Spontaneous Sy...mentioning
confidence: 99%
See 3 more Smart Citations